Cell-type specific mechanisms of D-serine uptake and release in the brain - Martineau, Magalie; Parpura, Vladimir; Mothet, Jean-Pierre (Frontiers in Synaptic Neuroscience, 2014)
Accumulating evidence during the last decade established that D-serine is a key signaling molecule utilized by neurons and astroglia in the mammalian central nervous system. D-serine is increasingly appreciated as the main physiological endogenous coagonist for synaptic NMDA receptors at central excitatory synapses; it is mandatory for long-term changes in synaptic strength, memory, learning, and social interactions. Alterations in the extracellular levels of D-serine leading to disrupted cell-cell signaling are a trademark of many chronic or acute neurological (i.e. Alzheimer disease, epilepsy, stroke) and psychiatric (i.e. schizophrenia) disorders, and are associated with addictive behavior (i.e. cocaine addiction). Indeed, fine tuning of the extracellular levels of D-serine, achieved by various molecular machineries and signaling pathways, is necessary for maintenance of accurate NMDA receptor functions. Here, we review the experimental data supporting the notion that astroglia and neurons use different pathways to regulate levels of extracellular D-serine.